Study on the optimization of VMS location based on drivers’ guidance compliance behaviors - Zhong, Shiquan; Zhou, Lizhen; Ma, Shoufeng; Wang, Xuelian; Jia, Ning (Transport, 2014)
Traffic guidance compliance behavior is influenced by many factors. The present study investigates the effect of Variable Message Sign (VMS) location on guidance compliance behaviors of drivers. Based on the State, Operator, and Result (SOAR) cognitive architecture, a SOAR agent framework of drivers’ traffic guidance compliance behavior is developed. The formation mechanism and the changes in the law of traffic guidance compliance behaviors of drivers, as well as the key factors of VMS location that affect drivers’ compliance behaviors are studied. These factors include the visual perception of drivers, memory representation, decision cycle, and learning mechanisms. Finally, traffic guidance compliance behavior based on the SOAR cognitive architecture is simulated multiple times to verify the effectiveness of different VMS locations. The simulation results show that setting the VMS a bit further away from the downstream intersection achieves better guidance effect.